Didactic proposal for learning the derivative with Derive - Pineda, Walter Byron; Hernández, Cesar Augusto; Avendaño, William Rodrigo (Universidad Pedagógica y Tecnológica de Colombia, 2020)
In this article, Derive is assessed according to its technical and pedagogical possibilities to facilitate students’ learning of differential calculus. The objective was to implement a methodological proposal in the teaching-learning process of the derivative of a functionin the initial training of mathematics teachers. The approach was quantitative, with a descriptive basis. The information collection instrument was the survey. We worked with a deliberate sample of 48 students from an initial teacher training program. The informationwas collected through a five options Likert-type questionnaire. The findings show the ease of access, the simplicity of the software and its pedagogical possibilities for proper usage of concepts associated with derivative applications. It is concluded that the adoption of Derivefacilitates the learning of derivatives, since it allows an appropriate usage of concepts and theories addressed in the methodological proposal.